2016
DOI: 10.1021/acs.jpclett.6b01412
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Humidity Delays Electron–Hole Recombination in Hybrid Organic–Inorganic Perovskites: Time-Domain Ab Initio Simulations Rationalize Experiments

Abstract: Experiments show both positive and negative changes in performance of hybrid organic-inorganic perovskite solar cells upon exposure to moisture. Ab initio nonadiabatic molecular dynamics reveals the influence of humidity on nonradiative electron-hole recombination. In small amounts, water molecules perturb perovskite surface and localize photoexcited electron close to the surface. Importantly, deep electron traps are avoided. The electron-hole overlap decreases, and the excited state lifetime increases. In lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
148
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 68 publications
(163 reference statements)
5
148
0
Order By: Relevance
“…Ab initio NAMD combined with TDDFT were performed to investigate the influence of different levels of humidity on nonradiative electron‐hole recombination at the MAPbI 3 (001) surface with a varying number of adsorbed water molecules . The study demonstrated that moderate humidity extends the excited‐state lifetime, while heavy humidity reduces the lifetime, in agreement with experiments.…”
Section: Photoexcitation Dynamicssupporting
confidence: 60%
See 4 more Smart Citations
“…Ab initio NAMD combined with TDDFT were performed to investigate the influence of different levels of humidity on nonradiative electron‐hole recombination at the MAPbI 3 (001) surface with a varying number of adsorbed water molecules . The study demonstrated that moderate humidity extends the excited‐state lifetime, while heavy humidity reduces the lifetime, in agreement with experiments.…”
Section: Photoexcitation Dynamicssupporting
confidence: 60%
“…We show why a grain boundary accelerates charge recombination in the CH 3 NH 3 PbI 3 (MAPbI 3 ) perovskite, and why chlorine passivation of the boundary extends the excited‐state lifetime . We demonstrate that moderate humidity delays electron‐hole recombination in MAPbI 3 and that heavy humidity accelerates the recombination . We analyze in detail how dopants control electron‐hole recombination at a MAPbI 3 /TiO 2 interface and suggest a route to suppress the charge and energy losses via a rational choice of dopants .…”
Section: Photoexcitation Dynamicsmentioning
confidence: 93%
See 3 more Smart Citations